Labour migration and alternate avocation in marine fisheries sector of Kerala - Shyam. S. Salim; M. Ramees Rahman and N. R. Athira (J. Mar. Biol. Ass. India, 2017)
The migration of labour has become an important feature of the globalizing world, accompanied with many economic, social and political concerns. Income inequalities, climate change, demographic shift and conflicts had contributed much for the migration of labour in search of employment and security. Hence a study over the labour migration as an adaptive or coping strategy has its own relevance in the current scenario. This study is an investigative research over the labour migration and alternative avocation in the marine fisheries sector. Marine fisheries sector is one of the most important sectors in India contributing much for the economy, still facing disguised unemployment. The study attempts to estimate the pros and cons of labour migration in the marine fisheries sector by analyzing the cases of fisher folks from various part of the country who migrated to Kerala coast. The empirical evidence presented in the paper explores the reasons, problems, income and savings and the seasonality of the migrants.